Discovery of highly potent heme-displacing IDO1 inhibitors based on a spirofused bicyclic scaffold. (1st February 2021) - Kinzel, Olaf; Steeneck, Christoph; Anderhub, Simon; Hornberger, Martin; Pinto, Sheena; Morschhaeuser, Barbara; Albers, Michael; Sonnek, Christina; Wang, Yansong; Mallinger, Aurélie; Czekańska, Marta; Hoffmann, Thomas
Graphical abstract: Abstract: Through structural modification of an oxalamide derived chemotype, a novel class of highly potent, orally bioavailable IDO1-specific inhibitors was identified. Representative compound 18 inhibited human IDO1 with IC50 values of 3.9 nM and 52 nM in a cellular and human whole blood assay, respectively. In vitro assessment of the ADME properties of 18 demonstrated very high metabolic stability. Pharmacokinetic profiling in mice showed a significantly reduced clearance compared to the oxalamides. In a mouse pharmacodynamic model 18 nearly completely suppressed lipopolysaccharide-induced kynurenine production. Hepatocyte data of 18 suggest the human clearance to be in a similar range to linrodostat (1 ).